Polyamide composites with improved thermal conductivity for effective thermal management: The three-dimensional vertically aligned carbon network. (1st November 2021) - Xu, Tongle; Zhou, Shuaishuai; Jiang, Fang; Song, Na; Shi, Liyi; Ding, Peng
Abstract: Carbon-based polymer composites with excellent thermal conductivity are highly desired in thermal management materials. However, the thermal conductivity enhancement of carbon-based polymer composites is limited, which are mostly caused by defects of fillers, unsatisfactory distribution and inferior interface between carbon fillers and matrix. Herein, we prepared polyamide composites with three-dimensional (3D) vertically aligned carbon network. The vertically aligned structure demonstrates a through-plane thermal conductivity up to 1.45 W m −1 K −1 at 5.2 wt% carbon fillers content, which is 644% higher than that of matrix. Moreover, through the regulated surface modification of carbon fillers, the carbon fiber with lower defect density and improved interfacial compatibility were obtained. The vertically aligned structure could take advantage of the intrinsic properties of carbon fillers and effectively reduce thermal contact resistance. The fabricated polyamide composites could be employed to dissipate excessive heat in thermal management system, and effectively reduce the working temperature of CPU. The design principles and preparation techniques in this work could also be applied to other carbon-based composites to surmount difficulties in effective thermal management of modern electronics.